Democracy in America $1 (BVolume 1s - Tocqueville, Alexis de, 1805-1859; Reeve, Henry, 1813-1895 (Salt Lake City, UT : Project Gutenberg, 2006)
"Democracy in America $1 (BVolume 1" by Alexis de Tocqueville is a classic French work published in 1835. After visiting America in 1831 to study prisons, Tocqueville turned his observations into an examination of democracy and equality in early nineteenth-century American society. He analyzes how religion, politics, and economics shaped the nation's egalitarian culture, while questioning the costs of social mobility and restlessness. The work explores democracy as both an American example and a broader revolutionary force transforming the Western world. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Democracy_in_America
Release date is 2006-01-21
David Reed and David Widger
Keywords: United States -- Politics and government; United States -- Social conditions; Democracy -- United States